Peran Masjid dalam Meningkatkan Rasa Cinta Lingkungan di Masjid Darul Haq Jl. Tuan Guru Suman Tembung - Arlina, Arlina; Alwi Umar Batubara; Dwi Nur Luthfiah; Fithri Asmelia; Khoridatunnida (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the program created by the mosque to increase the community's love of the environment. At the Darul Haq Mosque Jl. Master Suman Tembung. The research method used is qualitative based on phenomenological studies. The data collection techniques used were observation, interviews and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The results of the research explained that at the Darul Haq mosque the mosque marbot was used as a program called PM (Mosque Cleaner) which focused on maintaining the cleanliness of the Darul Mosque. Haq, PM at the Darul Haq mosque consists of 5 mosque teenagers who are given the mandate to clean their respective work areas or sectors which must be cleaned every day, both morning and evening. In an effort to increase the feeling of love for the mosque environment, everyone has the same duties and obligations, especially mosque youth, which in this modern era is an organization that really thinks about the development of Islam in an association or association that tends to love the mosque, in other words, to make the mosque prosperous and wants to train Get used to it. This program is accommodated directly by BKM (Mosque Prosperity Agency) Darul Haq which directs mosque teenagers who are the perpetrators of its activities.